1996
DOI: 10.1210/endo.137.8.8754734
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-stimulating hormone inhibits Fas antigen-mediated apoptosis of human thyrocytes in vitro.

Abstract: The mechanisms of TSH-induced growth stimulation of thyrocytes in vivo have yet to be elucidated. We examined the antiapoptotic effect of TSH toward Fas antigen-mediated apoptosis of thyrocytes. Fas antigen was expressed on approximately 40% of unstimulated thyrocytes, and the expression was significantly inhibited by the addition of TSH in a dose-dependent manner. Treatment of thyrocytes with 8-bromo-cAMP mimicked the effect of TSH, suggesting that the inhibitory effect of TSH on Fas antigen expression was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 31 publications
6
68
1
1
Order By: Relevance
“…Among these, Fas has been identified as the putative molecule capable of transducing apoptotic signals into cells [6]. We have recently reported that Fas is functionally expressed on thyrocytes and that anti-Fas-induced apoptosis of thyrocytes is significantly suppressed by treating cells with TSH [7]. Our data indicated that the growth-promoting activity of TSH on the thyroid glands may, in part, be achieved by the inhibitory effect of Fas-mediated apoptosis of thyrocytes.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…Among these, Fas has been identified as the putative molecule capable of transducing apoptotic signals into cells [6]. We have recently reported that Fas is functionally expressed on thyrocytes and that anti-Fas-induced apoptosis of thyrocytes is significantly suppressed by treating cells with TSH [7]. Our data indicated that the growth-promoting activity of TSH on the thyroid glands may, in part, be achieved by the inhibitory effect of Fas-mediated apoptosis of thyrocytes.…”
Section: Introductionmentioning
confidence: 59%
“…The experimental protocol was approved by the Hospital Human Ethics Review Committee and a signed consent was obtained from each patient. The method used for the isolation of thyrocytes was described previously in detail [7,17]. The resultant thyrocyte preparations were < 1% reactive with MoAbs, CD3, CD20, CD14, and anti-von Willebrand factor, which, respectively, define an antigen on all mature T cells, pan-B cells, monocytes/macrophages, and on vascular endothelial cells.…”
Section: Preparation Of Thyrocytesmentioning
confidence: 99%
See 3 more Smart Citations